Global Liquidity, House Prices, and the Macroeconomy : Evidence from Advanced and Emerging Economies - Cesa-Bianchi, Ambrogio; Cespedes, Luis Felipe; Rebucci, Alessandro (Washington, D.C. : International Monetary Fund, 2015)
In this paper we first compare house price cycles in advanced and emerging economies using a new quarterly house price data set covering the period 1990-2012. We find that house prices in emerging economies grow faster, are more volatile, less persistent and less synchronized across countries than in advanced economies. We also find that they correlate with capital flows more closely than in advanced economies. We then condition the analysis on an exogenous change to a particular component of capital flows. We find that a global liquidity shock, identified by aggregating bank-to-bank cross border flows and by using the external instrumental variable approach of Stock and Watson (2012) and Mertens and Ravn (2013), has a much stronger impact on house prices and consumption in emerging markets than in advanced economies. In our empirical model, holding house prices or the exchange rate constant in response to this shock tends to dampen its effects on consumption in emerging economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet